ANALISIS FRAMING BERITA SERANGAN ISIS DI PARIS PADA SURAT KABAR HARIAN WASPADA, SIB DAN ANALISA - Desiana Desiana (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
This paper explains the construction of reality preaching attacks ISIS in Paris at daily newspapers Alert, SIB, and Analysis edition of 15 to 30 November 2015 explained that in the daily Alert reality construction preaching leads to religious issues, with regard attacks ISIS in Paris had an adverse impact against Muslims. Construction of reality in the daily SIB lead to political problems, with regard ISIS as a radical group resistance against France. While construction of reality daily news analysis leads to political and social issues with regard attacks in Paris as an act of war against the French ISIS, which impose heavy casualties as well as implications for the Middle East refugees (Middle East) who are in Europe.Based on the analysis of the news reality construction it can be seen the results of the analysis of differences in framing news ISIS attacks in Paris of the three newspapers. On Alert daily use frames because the religious field as daily newspapers Islami, the delivery of his message focused on religious issues. In contrast to the daily SIB that raised political issues, so the frames used SIB is to frame the political field. Meanwhile, as the newspaper is neutral analysis using a frame political and social news ISIS attacks in Paris